Finding qualitative research: an evaluation of search strategies - Shaw, Rachel L (BioMed Central, 2004)
BACKGROUND: Qualitative research makes an important contribution to our understanding of health and healthcare. However, qualitative evidence can be difficult to search for and identify, and the effectiveness of different types of search strategies is unknown. METHODS: Three search strategies for qualitative research in the example area of support for breast-feeding were evaluated using six electronic bibliographic databases. The strategies were based on using thesaurus terms, free-text terms and broad-based terms. These strategies were combined with recognised search terms for support for breast-feeding previously used in a Cochrane review. For each strategy, we evaluated the recall (potentially relevant records found) and precision (actually relevant records found). RESULTS: A total yield of 7420 potentially relevant records was retrieved by the three strategies combined. Of these, 262 were judged relevant. Using one strategy alone would miss relevant records. The broad-based strategy had the highest recall and the thesaurus strategy the highest precision. Precision was generally poor: 96% of records initially identified as potentially relevant were deemed irrelevant. Searching for qualitative research involves trade-offs between recall and precision. CONCLUSIONS: These findings confirm that strategies that attempt to maximise the number of potentially relevant records found are likely to result in a large number of false positives. The findings also suggest that a range of search terms is required to optimise searching for qualitative evidence. This underlines the problems of current methods for indexing qualitative research in bibliographic databases and indicates where improvements need to be made.